Environment-friendly binding agent for blast furnace stemming, preparation method and environment-friendly anhydrous stemming
By using environmentally friendly bonding agents composed of decrystallized anthracene oil, low-temperature modified asphalt, etc., the problems of poor plasticity and high benzopyrene content of existing blast furnace gun mud bonding agents are solved, and environmentally friendly anhydrous gun mud with good plasticity and high temperature stability are prepared, which significantly improves the construction performance and environmental friendliness of gun mud.
Patent Information
- Application Number
- CN202411940142.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
AI Technical Summary
The binding agents of existing blast furnace cannon mud have problems such as poor plasticity, too fast coking, short shelf life and high benzopyrene content, which limits its application in blast furnaces.
An environmentally friendly bonding agent composed of decrystallized anthracene oil, low-temperature modified asphalt, pine tar, thermoplastic resin and tetraethyl orthosilicate is used to remove moisture and volatile components through high-temperature treatment and cyclic stirring to prepare environmentally friendly anhydrous cannon mud with good plasticity and high-temperature stability.
It significantly improves the construction performance, plasticity and high-temperature mechanical properties of gun mud, reduces the benzopyrene content, extends the service life, and reduces environmental pollution.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metallurgy, and in particular relates to an environmentally friendly binder for blast furnace taphole mud, a preparation method and environmentally friendly anhydrous taphole mud. Background Art
[0002] Taphole clay is a functional refractory material used to plug the taphole of a blast furnace. With the development of blast furnace technology, blast furnaces are gradually moving towards high air volume, high oxygen enrichment, high top pressure and high coal ratio, which puts higher requirements on the performance of anhydrous taphole clay. At present, the new goal of global ironmaking is low cost, high efficiency, energy saving and environmental protection. These smelting conditions make the application requirements of taphole clay more stringent, and people are gradually beginning to pay attention to the environmental protection and durability of taphole clay.
[0003] Waterless taphole mud should not only have good plasticity and be easy to construct, but also have excellent resistance to erosion and scouring of slag iron. The traditional taphole mud combined with coal tar and coal tar contains strong carcinogen benzopyrene, which is extremely harmful, and the yellow smoke emission seriously pollutes the environment. In order to protect the environment and human health, it is urgent to develop environmentally friendly taphole mud with low or no benzopyrene content and promote its industrialization to meet the needs of the modern steel industry.
[0004] The taphole mud prepared using resin has problems such as poor plasticity, rapid coking, difficulty in preservation, low high temperature strength and poor iron mouth depth, which limit its application in the field of taphole mud. Chinese patent CN 106145966 B discloses a binder for blast furnace taphole mud, which includes 40-70 parts of coal tar distillation kettle bottoms, 30-60 parts of phenolic varnish resin and 2-5 parts of surfactant. Another Chinese patent CN 102875178 B provides a binder for large blast furnace taphole mud, which uses silicone resin, furan resin and melamine formaldehyde resin as a curing component and hydrogenated terphenyl as a synergist. The binder has high plasticity and low curing rate, which is conducive to improving the fluidity of taphole mud at high temperature and overcoming the disadvantage of easy agglomeration of traditional taphole mud. However, after the three resins in the binder are compounded, there are problems of short product shelf life and poor practicality.
[0005] Based on this, it is of great practical significance to develop an environmentally friendly taphole mud with simple process, good plasticity, excellent performance and strong thermal stability. This kind of taphole mud has extremely low benzopyrene content at high temperature, which can significantly improve the construction performance of taphole mud and the on-site working environment. Summary of the invention
[0006] The first technical problem to be solved by the present invention is to provide an environmentally friendly binder for blast furnace cannon mud, which has high residual carbon content, low viscosity, good dispersibility, extremely low moisture content and benzopyrene content; the second technical problem to be solved by the present invention is to provide a preparation method of an environmentally friendly binder for blast furnace cannon mud, which has a simple process and is suitable for large-scale industrial applications; the third technical problem to be solved by the present invention is to provide an environmentally friendly anhydrous cannon mud prepared with an environmentally friendly binder, which has good working performance and plasticity, is easy to open, has excellent mechanical properties at high temperatures, and has high corrosion resistance.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0008] An environmentally friendly binder for blast furnace taphole mud is prepared from the following components in parts by weight: 40-50 parts of decrystallized anthracene oil, 10-20 parts of low-temperature reformed asphalt, 10-20 parts of pine tar, 20-30 parts of thermoplastic resin, and 0-1 part of tetraethyl orthosilicate.
[0009] The decrystallized anthracene oil has a kinematic viscosity of 50-150 centipoise at 60° C. and a water content of ≤3.0%.
[0010] The thermoplastic resin has a molecular weight of 75,000-90,000, a kinematic viscosity of 200-350 centipoise at 60°C, and a carbon residue value of ≥50.00 wt% after reacting at 900°C for 10 min.
[0011] The tetraethyl orthosilicate is used as a viscosity reducing agent, and the moisture content is ≤5.0%.
[0012] The fixed carbon of the low-temperature reformed asphalt is ≥70%, and the softening temperature is 80~100°C.
[0013] The method for preparing the environmentally friendly binder for blast furnace taphole mud described in any one of the above items comprises the following steps:
[0014] (1) Add decrystallized anthracene oil, pine tar oil and thermoplastic resin into a reactor according to the proportion, the stirring speed of the reactor is 60-100 rpm, and the heating temperature is 120-150 °C;
[0015] (2) After the temperature of the reactor reaches 120-150 °C, add low-temperature reformed asphalt into the reactor, completely dissolve the reformed asphalt in the binder, and add tetraethyl orthosilicate in proportion;
[0016] (3) The binder is kept at 120 °C for 2 h to ensure that the modified asphalt is completely dissolved, and the binder is prepared after removing the water and some volatiles. The temperature is then lowered to 60 °C and stirred for standby use.
[0017] The present invention also provides an environmentally friendly anhydrous taphole clay for blast furnaces, comprising the environmentally friendly binder for blast furnace taphole clay described in the present invention.
[0018] The environmentally friendly anhydrous taphole mud for blast furnace comprises the following components in parts by weight: 8-16 parts of porcelain sand with a particle size of 1-3 mm, 8-16 parts of brown corundum with a particle size of 0-1 mm, 7-15 parts of kyanite with a particle size not greater than 1 mm, 7-15 parts of silicon carbide with a particle size of 1-3 mm, 10-20 parts of 325 mesh silicon carbide dust removal powder, 8-16 parts of 200 mesh silicon nitride iron, 4-8 parts of 200 mesh ball clay, 8-16 parts of 200 mesh brown corundum, 2-4 parts of alumina micropowder, 2-4 parts of graphite, 1-3 parts of phenolic resin powder, and 1-2 parts of ferrosilicon powder.
[0019] The porcelain sand is an aggregate, and the Al2O3 content is ≥80%.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] (1) The decrystallized anthracene oil used in the present invention exhibits excellent high-temperature strength in a high-temperature environment and can maintain good stability, ensuring that the taphole mud does not experience performance degradation or structural damage at high temperatures. This high-temperature stability enables it to effectively withstand extreme temperature changes during the smelting process and ensure the smooth operation of the blast furnace. In addition, the decrystallized anthracene oil also has excellent adhesion, which can effectively bond the various components in the taphole mud to form a solid structure. This feature not only enhances the overall strength of the taphole mud, but also improves its durability, reduces damage and deterioration caused by factors such as high temperature and friction, thereby extending its service life. The environmental friendliness of the decrystallized anthracene oil is also one of its important characteristics. Compared with traditional coal tar, the decrystallized anthracene oil has less waste gas and wastewater emissions, which meets the environmental protection requirements of modern industry. During use, the decrystallized anthracene oil will not release harmful substances, has little impact on the environment, and helps to reduce the negative impact on the ecosystem. At the same time, the production cost of the decrystallized anthracene oil is low, and the raw materials are easily available and the process is simple. As a taphole mud binder, it not only has excellent performance, but also can effectively reduce production costs. It is particularly suitable for large-scale industrial applications and has broad market competitiveness.
[0022] (2) When the present invention uses pine tar as a binder, the release of benzopyrene can be reduced, which is of great significance for reducing blast furnace environmental pollution and protecting workers' health.
[0023] (3) The low-temperature modified asphalt of the present invention has good coking performance and thermal stability. When asphalt is added to the cannon clay, it undergoes a carbonization process at high temperature, which significantly increases the residual carbon content of the cannon clay, thereby improving its high-temperature performance, mechanical properties, corrosion resistance and scouring resistance. The asphalt also increases the antioxidant capacity of the cannon clay and delays the performance degradation caused by oxidation. The low-temperature modified asphalt can dissolve into the binder, effectively disperse the material and fill the gaps, and enhance the bonding strength of the cannon clay. At the same time, the lubricating properties of the asphalt improve the plasticity of the cannon clay, improve its operability and molding performance, and through dissolution at high temperature, the modified asphalt significantly increases the residual carbon content of the binder, enhances its bonding strength and carbonization rate, and ensures that the cannon clay still maintains a stable structure and excellent performance under high temperature conditions. The uniform dispersion of the modified asphalt in the binder not only improves the corrosion resistance and wear resistance, but also improves the structural strength, ensuring the efficient and long-term use of the cannon clay in production. In addition, the excellent bonding properties of modified asphalt effectively delay the premature hardening and condensation of cannon mud, extend its service life, and maintain good performance in long-term use. Its lubricating effect also effectively reduces the friction between materials, improves the fluidity and processability of cannon mud, thereby improving the overall performance.
[0024] (4) The thermoplastic resin of the present invention has good plasticity, can improve the fluidity and processing performance of the cannon clay, facilitate molding and reduce defects. The molecular structure of the resin has high ductility and impact resistance, can improve the impact resistance and medium-temperature flexural strength of the cannon clay, and reduce the risk of cracks or fractures caused by external forces. The thermoplastic resin toughened epoxy resin significantly improves the activity of the molecular network and enhances the toughness of the resin by adjusting the chemical structure of the cross-linked network, especially playing an effective restraining role in crack propagation. The resin prevents the continued expansion of the cracks by crossing the cracks inside the epoxy resin matrix, thereby effectively inhibiting the growth of the cracks. In addition, the use of thermoplastic resin as a binder solves the problems of short cannon clay shelf life, severe coking and poor anti-scouring performance caused by high cross-linking density and fast curing speed of traditional phenolic resin.
[0025] (5) The present invention performs high-temperature treatment and cyclic stirring on the binder in the reactor, effectively removing the moisture and volatile components therein. This process not only improves the dispersibility of the binder, making it more evenly distributed in the matrix during use, but also reduces the structural defects that may occur during the sintering process. By controlling the moisture content, the negative impact of excessive moisture on the performance of the taphole mud is avoided, thereby improving its stability and durability, and ensuring excellent performance under high temperature conditions. This treatment effectively optimizes the physical and chemical properties of the binder and provides a more reliable guarantee for the use of the taphole mud.
[0026] (6) The present invention uses tetraethyl orthosilicate as a raw material, which significantly reduces the viscosity of the binder, reduces its usage, and improves the plasticity of the taphole mud. By reducing the viscosity, the wettability and fluidity of the binder are improved, so that the taphole mud aggregate particles can be more evenly dispersed, and the bonding force between the taphole mud and the matrix is enhanced. This improvement not only optimizes the processing performance of the taphole mud, making it easier to shape, but also significantly improves the plasticity and fluidity of the taphole mud, thereby enhancing its stability and adaptability under high temperature and complex working conditions.
[0027] (7) The present invention uses porcelain sand as aggregate, which has the advantages of low oil absorption, stable performance and quality, and low cost. Its dense structure and low apparent porosity make porcelain sand play an important role in cannon mud. The use of porcelain sand not only improves the uniformity of cannon mud, but also significantly reduces the amount of oil added to cannon mud due to its low oil absorption rate. Therefore, the plasticity and strength of cannon mud are enhanced, further improving its performance and durability in practical applications. DETAILED DESCRIPTION
[0028] The present invention is further illustrated below in conjunction with specific examples. The examples are implemented based on the technical solutions of the present invention. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0029] The decrystallized anthracene oil used in the following examples has a kinematic viscosity of 50-150 centipoise at 60°C and a moisture content of ≤3.0%; the thermoplastic resin has a molecular weight between 75,000 and 90,000, a kinematic viscosity of 200-350 centipoise at 60°C, a carbon residue value ≥50.00 wt% detected at 900°C×10 min, and a moisture content ≤5.0%; tetraethyl orthosilicate is used as a viscosity reducer with a moisture content ≤5.0%; low-temperature reformed asphalt has a fixed carbon content ≥70% and a softening temperature ≤100°C; porcelain sand is used as aggregate with an Al2O3 content ≥80%.
[0030] Example 1
[0031] 1. An environmentally friendly binder for blast furnace taphole mud, comprising the following components in parts by weight:
[0032]
[0033] 2. A method for preparing an environmentally friendly binder for blast furnace taphole mud:
[0034] (1) Pine tar oil, decrystallized anthracene oil and thermoplastic resin are added into a reactor in proportion. The stirring speed of the reactor is in the range of 60-100 rpm and the reaction temperature is in the range of 120-150 °C.
[0035] (2) After the reactor temperature reaches 120-150 °C, add low-temperature reformed asphalt into the reactor, completely dissolve the reformed asphalt in the binder, and add ethyl orthosilicate in proportion.
[0036] (3) The binder is kept at 120 °C for 2 h to ensure that the modified asphalt is completely dissolved, and the binder is prepared after removing the water and some volatiles. The temperature is then lowered to 60 °C and stirred for standby use.
[0037] 3. A blast furnace environmentally friendly taphole mud is composed of the following components in parts by weight:
[0038]
[0039] 4. Preparation method of taphole mud:
[0040] 1) Weigh the above solid powder according to the proportion, add the aggregate into the mixer, mix and grind for 5 minutes, and then add 1 / 3 of the homemade environmentally friendly binder;
[0041] 2) Premix the powder in a premixing tank for 30 minutes to ensure that the premixed powder is evenly mixed;
[0042] 3) Put the premixed powder mixed evenly in the premix tank into the mixer and mix it with the aggregate for 5 minutes, then add 1 / 3 of the homemade environmentally friendly binder;
[0043] 4) After continuing to mix and grind for 30 min, add the remaining 1 / 3 of the homemade environmentally friendly binder, mix and grind for 10 min and then discharge the material. The discharge temperature is controlled at 60-70 °C, and the material is extruded, cut into pieces, and plastic-sealed for packaging. The amount of the homemade environmentally friendly binder added to the anhydrous cannon mud is controlled at 10-11%, and the Marshal value is controlled at 1300 kPa.
[0044] Example 2
[0045] 1. An environmentally friendly binder for blast furnace taphole mud, comprising the following components in parts by weight:
[0046]
[0047] 2. A method for preparing an environmentally friendly binder for blast furnace taphole mud is the same as Example 1 to obtain an environmentally friendly binder.
[0048] 3. A blast furnace environmentally friendly taphole mud is composed of the following components in parts by weight:
[0049]
[0050] 4. The method for preparing taphole clay is the same as that in Example 1 to obtain water-free and environmentally friendly taphole clay.
[0051] Example 3
[0052] 1. An environmentally friendly binder for blast furnace taphole mud, comprising the following components in parts by weight:
[0053]
[0054] 2. A method for preparing an environmentally friendly binder for blast furnace taphole mud is the same as Example 1 to obtain an environmentally friendly binder.
[0055] 3. A blast furnace environmentally friendly taphole mud is composed of the following components in parts by weight:
[0056]
[0057] 4. The method for preparing taphole clay is the same as that in Example 1 to obtain water-free and environmentally friendly taphole clay.
[0058] Example 4
[0059] 1. An environmentally friendly binder for blast furnace taphole mud, comprising the following components in parts by weight:
[0060]
[0061] 2. A method for preparing an environmentally friendly binder for blast furnace taphole mud is the same as Example 1 to obtain an environmentally friendly binder.
[0062] 3. A blast furnace environmentally friendly taphole mud is composed of the following components in parts by weight:
[0063]
[0064] 4. The method for preparing taphole clay is the same as that in Example 1 to obtain water-free and environmentally friendly taphole clay.
[0065] Example 5
[0066] 1. An environmentally friendly binder for blast furnace taphole mud, comprising the following components in parts by weight:
[0067]
[0068] 2. A method for preparing an environmentally friendly binder for blast furnace taphole mud is the same as Example 1 to obtain an environmentally friendly binder.
[0069] 3. A blast furnace environmentally friendly taphole mud is composed of the following components in parts by weight:
[0070]
[0071] 4. The method for preparing taphole clay is the same as that in Example 1 to obtain water-free and environmentally friendly taphole clay.
[0072] Comparative Example 1
[0073] 1. Use coal tar as a binder
[0074] 2. A blast furnace environmentally friendly taphole mud is composed of the following components in parts by weight:
[0075]
[0076] 3. Preparation method of taphole mud
[0077] 1) Weigh the above solid powder according to the proportion, add the aggregate into the mixer, mix and grind for 5 minutes, and then add 1 / 3 of the tar binder;
[0078] 2) Premix the powder in a premixing tank for 30 minutes to ensure that the premixed powder is evenly mixed;
[0079] 3) Put the premixed powder mixed evenly in the premixing tank into the mixer and mix it with the aggregate for 5 minutes, then add 1 / 3 of tar;
[0080] 4) After continuing to mix and grind for 30 minutes, add the remaining 1 / 3 of tar, mix and grind for 10 minutes and then discharge the material. The discharge temperature is controlled at 60-70 °C, and the material is extruded, cut into pieces, and plastic-sealed for packaging. The amount of tar binder added to the anhydrous taphole mud is controlled at 10-11%, and the Marshal value is controlled at 1300 kPa.
[0081] The performance of the anhydrous cannon clay prepared in Examples 1 to 5 and Comparative Example 1 was tested. A 40 mm × 40 mm × 160 mm mold was prepared, the surface was cleaned and evenly coated with lubricating oil, the prepared anhydrous cannon clay was placed in the mold, and placed in the center of the pressure testing machine operating table to press with a pressure of 45 kN, and the pressure was maintained for 30 s; after demolding, it was placed at room temperature for 48 h, heated to 1500 ° C, and stopped heating after 3 h of charcoal heat treatment, and the sample was taken out after natural cooling to room temperature with the furnace, and the sample was tested, wherein: the volume density and apparent porosity of the cannon clay after calcination at 1500 ° C were tested with reference to GB / T 2997-2000; the compressive strength and flexural strength of the cannon clay after calcination were tested with a microcomputer-controlled electro-hydraulic servo universal testing machine, and the linear change rate = (L 处理后 -L 初始 ) / L 初始 ×100% to calculate the linear change rate of taphole mud. The results are shown in Table 1.
[0082] Table 1 Performance indexes of anhydrous taphole mud prepared in Examples 1 to 5 and Comparative Example 1 after burning at 1500°C
[0083]
[0084] Compared with the prior art, this specific implementation has the following positive effects:
[0085] The environmentally friendly tar used in the present invention has a low benzopyrene content, which greatly reduces the generation of carcinogens or pollutants such as benzopyrene and aldehydes during the use of the taphole mud, and significantly reduces the pollution to the environment and the harm to the workers in front of the furnace. The present invention adopts a circulating stirring process under 120-150 ° C under normal pressure, with high safety performance, simple process, low labor intensity and high production efficiency. The blast furnace taphole mud of the present invention uses a high-performance binder, and liquid resin is added to the binder, which significantly improves the residual carbon, coking value and β resin content of the binder, thereby improving the use performance of the binder and improving the instability problem caused by the complex composition of ordinary tar. At the same time, the addition of liquid resin is conducive to improving the plasticity of the taphole mud and reducing the amount of the binder. After the liquid resin is added to the binder, the plasticity of the taphole mud is significantly improved, so that it can be smoothly pressed into the iron mouth channel without looseness and holes, ensuring that the iron mouth channel is full, no molten iron is mixed in and the iron mouth mud bag is formed when the mouth is blocked, and sufficient iron mouth depth is ensured. When pine tar is used as a binder, the release of benzopyrene can be reduced, which is of great significance for reducing blast furnace environmental pollution and protecting the health of workers. The added decrystallized anthracene oil has excellent high-temperature strength and stability, and can effectively withstand extreme temperature changes in high-temperature environments, ensuring that the cannon mud does not experience performance degradation or structural damage. It has strong adhesion, can enhance the strength and durability of the cannon mud, and reduce damage caused by high temperature and friction. Compared with traditional coal tar, decrystallized anthracene oil is more environmentally friendly, has less emissions, and has a lower production cost, making it suitable for large-scale industrial applications. The modified asphalt incorporated has good coking performance, thermal stability and antioxidant ability. After being added to the cannon mud, it can increase the residual carbon content, improve high-temperature performance, mechanical properties and corrosion resistance, and delay the performance degradation caused by the oxidation process. Low-temperature modified asphalt also enhances the bonding strength and plasticity of the cannon mud, improves operability and formability, and extends its service life. Tetraethyl orthosilicate is added to the binder to reduce the viscosity of the binder, improve fluidity and wettability, enhance the plasticity and stability of the cannon mud, make it perform better under high temperature and complex working conditions, and reduce the amount used. The addition of porcelain sand as aggregate to the cannon mud has the characteristics of low oil absorption, good stability, and low cost. It can improve the uniformity and strength of the cannon mud, reduce the amount of oil used, and thus improve the performance and durability of the cannon mud. The anhydrous cannon mud prepared using this binder has good working performance, excellent plasticity, easy opening, and significantly improved mechanical properties and corrosion resistance at high temperatures. The benzopyrene content in the prepared cannon mud is less than 50 ppm, the on-site operating environment is significantly improved, and there is no obvious irritation of smoke generation.
[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An environmentally friendly binder for blast furnace taphole mud, characterized in that: The invention is prepared from the following components in parts by weight: 40-50 parts of decrystallized anthracene oil, 10-20 parts of low-temperature reformed asphalt, 10-20 parts of pine tar oil, 20-30 parts of thermoplastic resin and 0-1 part of tetraethyl orthosilicate.
2. The environmentally friendly binder for blast furnace taphole mud according to claim 1, characterized in that: The decrystallized anthracene oil has a kinematic viscosity of 50-150 centipoise at 60° C. and a water content of ≤3.0%.
3. The environmentally friendly binder for blast furnace taphole mud according to claim 1, characterized in that: The thermoplastic resin has a molecular weight of 75,000-90,000, a kinematic viscosity of 200-350 centipoise at 60°C, and a carbon residue value of ≥50.00 wt% after reacting at 900°C for 10 min.
4. The environmentally friendly binder for blast furnace taphole mud according to claim 1, characterized in that: The tetraethyl orthosilicate is used as a viscosity reducing agent, and the moisture content is ≤5.0%.
5. The environmentally friendly binder for blast furnace taphole mud according to claim 1, characterized in that: The fixed carbon of the low-temperature reformed asphalt is ≥70%, and the softening temperature is 80~100°C.
6. The method for preparing an environmentally friendly binder for blast furnace taphole mud according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Add decrystallized anthracene oil, pine tar oil and thermoplastic resin into a reactor according to the proportion, the stirring speed of the reactor is 60-100 rpm, and the heating temperature is 120-150 °C; (2) After the temperature of the reactor reaches 120-150 °C, add low-temperature reformed asphalt into the reactor, completely dissolve the reformed asphalt in the binder, and add tetraethyl orthosilicate in proportion; (3) The binder is kept at 120 °C for 2 h to ensure that the modified asphalt is completely dissolved, and the binder is prepared after removing the water and some volatiles. The temperature is then lowered to 60 °C and stirred for standby use.
7. An environmentally friendly anhydrous taphole mud for blast furnace, characterized in that: Including the environmentally friendly binder for blast furnace taphole mud as described in claim 1.
8. The environmentally friendly anhydrous taphole mud for blast furnace according to claim 7, characterized in that: The environmentally friendly anhydrous taphole mud for blast furnace comprises the following components in parts by weight: 8-16 parts of porcelain sand with a particle size of 1-3 mm, 8-16 parts of brown corundum with a particle size of 0-1 mm, 7-15 parts of kyanite with a particle size not greater than 1 mm, 7-15 parts of silicon carbide with a particle size of 1-3 mm, 10-20 parts of 325 mesh silicon carbide dust removal powder, 8-16 parts of 200 mesh silicon nitride iron, 4-8 parts of 200 mesh ball clay, 8-16 parts of 200 mesh brown corundum, 2-4 parts of alumina micropowder, 2-4 parts of graphite, 1-3 parts of phenolic resin powder, and 1-2 parts of ferrosilicon powder.
9. The environmentally friendly anhydrous taphole mud for blast furnace according to claim 8, characterized in that: The porcelain sand is an aggregate, and the Al2O3 content is ≥80%.
Citation Information
Patent Citations
Bonding agent for stemming of large-scale blast furnace
CN102875178B
A binder for blast furnace taphole clay and blast furnace taphole clay
CN106145966B